Anti-ulcer activity of aqueous extract murraya koenigii in albino rats - DINESH KUMAR PATIDAR (International Journal of Pharma and Bio Sciences, 2011)
The anti-ulcer effect of aqueous extract Murraya Koenigii was studied in Pylorus ligation and NSAIDs induced ulcer model in albino rats. The extract at dose of 200,400 mg/kg produced significant inhibition of gastric lesion induced by NSAIDs and Pylorus ligation induced ulcer. The extract reduced ulcerative lesion, gastric volume, free and total acidity but raised the PH of gastric juice in Pylorus ligation model. The result obtained suggesting that extract possesses significant anti-ulcer activity.